Multi-objective mathematical modeling for sustainable supply chain management in the paper industry - Vafaeenezhad, Taha; Tavakkoli-Moghaddam, Reza; Cheikhrouhou, Naoufel (Computers & industrial engineering, 2019)
•Considering new environmental and social factors in the sustainability context.•Considering real case constraints according to the novel case study from the paper industry.•Addressing operational and tactical supply chain planning under the sustainability paradigm.•Considering multi-period and multi-product problems. This work develops a multi-objective linear programming model for a multi-echelon, multi-product, multi-period supply chain planning. This model considers all dimensions of sustainable development paradigm simultaneously and expands six objective functions for making the model realistic. To solve this model and large-scale sustainable supply chain management, an improved version of the augmented ε-constraint method (AUGMECON2) is used. Computational results illustrate the proposed model admitted various progresses in all the three pillars of sustainable development; namely remarkable progress, mildly progress and irregular one, respectively. In addition, important managerial insights are provided. Trade-off interactions between multi-objectives are perceived by the obtained Pareto solutions that represents the cost of being sustainable from the point of optimizing the social factors and environmental impacts. An application to the paper industry is presented and discussed.